CRITICAL EXAMINATION OF THE IEET MEASUREMENT INSTRUMENT FOR THE ASSESSMENT OF TEXTBOOK QUALITY (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
As is the case in other sectors of the creative industry, the publishing industry also evaluates its projects finalized in the form of products and services in the market of creative contents. This paper aims to investigate the IEET measurement instrument that enables quality evaluation of products in the publishing industry. Quantitative research was conducted for the purpose of testing the main hypothesis of the study by which the quality of products in the book publishing industry features objectively measurable characteristics that can be determined by analysing user opinions. In this paper, an elementary school textbook has been selected as a publishing industry product and 147 respondents were involved in the research. Respondents, who evaluated the quality of the product by using the IEET measurement instrument, were selected according to the criterion of using a publishing industry product (textbook) in the educational process.After an exploratory factor analysis, the dimensions of the IEET measurement instrument were confirmed. A correlation analysis was applied to test the correlation between the identified dimensions and the most important textbook characteristics. The research results are critically reconsidered and can be utilised as guidelines for future research.